Potential for Increased Rural Electrification Rate in Sub-Saharan Africa using SWER Power Distribution Networks - Irechukwu, Michael E.; Mushi, Aviti T. (Tanzania Journal of Engineering and Technology, 2021)
Rural electrification rate (RER) in Africa is still low to date. Several countries in Sub-Saharan Africa have tried to address this problem using conventional single- phase two-wire or three-phase three-wire systems, however at large costs due to the nature of dispersed rural load centres, low load demand, and low population density. Another solution of off-grid generation creates associated health problems. Therefore, this paper undertakes a review of a single wire earth return (SWER) network as a RER improvement solution. The paper undertakes intensive literature review to elucidate challenges and solutions to the implementation of SWER technology. Advantages of SWER technology discussed make it the choice for RER improvement in Sub-Saharan African countries. After that, a case study is selected in rural Tanzania, and a preliminary SWER network design is undertaken. Keywords: Single wire earth return (SWER), power distribution networks, rural electrification rate (RER).